وجهي قرينة الدستورية ومبررات التقيد بها - Abdalyama, Abdulhameed; Bahjat, Maha (Journal of Legal Sciences, 2022)
The constitutional presumption is one of the controls on the constitutionality of laws. It has two aspects. First, the constitutional judiciary examines the interpretation that makes the legislation conform to the constitution. The second is to avoid ruling the constitutionality of legislation only in cases where the violation of the constitution is clear and categorical. And that the creation of the constitutional justice of this officer and adherence to it was not intended to favor or bias the legislator because this would undermine the independence of the constitutional judiciary, but there are justifications that prompted the constitutional judiciary to invent this officer is to take into account the practical considerations and the prevailing legal idea, and there are justifications that pushed this judiciary to adhere With this officer changing the view of the process of making legislation, and ensuring the achievement of legal security, and the impact of the constitutional judiciary on globalization.